Cortical imaging as seen at ultrahigh field MRI - Abdel-Fahim, Rasha (2017)
Multiple Sclerosis (MS) has long been considered as White matter (WM) disease. The last decade, the significance of cortical lesions (CL) and their contribution to MS pathology has been intensely investigated. They have been shown to play a major role in physical and cognitive impairment in MS patients. CL detection has proven to be challenging, mainly due to poor contrast between cortical lesion and surrounding normal grey matter (GM) tissue. Various magnetic resonance imaging (MRI) sequences have been used to improve cortical lesion detection in MS patients. In recent years, Double inversion recovery (DIR), Phase sensitive inversion recovery (PSIR) and 7 Tesla T2* have been found to improve CL detection. Magnetization Transfer Imaging (MTI) has the advantage over conventional imaging as it reflects tissue myelin content. In this thesis, I present our studies using MTI at 7 Tesla to study cortical pathology in MS.